PENERAPAN METODE PEMBELAJARAN COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA MATERI TIME KELAS VII.1 SMPN 18 PEKANBARU TAHUN 2017 - halmi, halmi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2018)
Abstract This study aims to determine the Application Of Course Review Horay Learning Method To Improve English Learning Results Students Of Time Class VII.1 in SMP Negeri 18 Pekanbaru. This form of research is a classroom action research with as many as two rounds (Cycle). Each round is done with four stages of planning, implementation, observation and reflection. The subjects of this study are the students of class VII.1 in SMP Negeri 18 Pekanbaru with a total of 36 students consisting of 19 male students and 17 female students. The data obtained in the form of English learning result obtained from the test and observation sheet of teaching and learning activities. Data collection methods used include test, observation and documentation. From the results in the first cycle of student learning outcomes to 40% with inactive classification. While in cycle II result of student in learning experience increase to become 60% with very active classification. This situation shows that improvements in English learning process with Course Review Horay learning model in English subjects in grade VII.1 students at SMP Negeri 18 Pekanbaru can be said to be fully successful. Keywords : English, Time, Course Review Horay